The Effect of Campus Facilities Quality and Technology Support on Student Satisfaction - Nayma, Salshabilla; Panjaitan, Cristanti; Silitonga, Claudia Jeremia; Aditya, Rizka Dina; Khofifah; Fachruddin, Wan (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
The aim of this research is to show how technological support and the quality of campus facilities influence student satisfaction at Panca Budi Development University. Data was collected from 58 respondents through a five-point Likert scale questionnaire. The independent variables, namely technology support and campus facilities, are related to the dependent variable, namely student satisfaction. This study was conducted using multiple linear regression analysis. Research shows that student satisfaction is significantly and positively influenced by technological support and campus facilities. Campus facilities have the smallest influence, but technology support has the greatest influence (regression coefficient 0.838). Simultaneously these two variables make a significant contribution to student satisfaction (E-count = 122.645; p < 0.05). With a coefficient of determination (R2) of 81.7%, this research shows that more technological support and campus facilities are needed to create an ideal learning environment and increase student satisfaction.